The Study of CRP as an Inflammatory Marker in Diabetes Mellitus with relation to the Level of Glycosylated Haemoglobin: A Case- Control Study - Yugantar N. Wakde; Richa K. Lath; Neetesh Kumar Jaiswal (The Bioscan, 2026)
Diabetes mellitus is a group of metabolic disorders characterized by hyperglycemia. According to several studies, it is noticed that diabetic patients have progressive inflammation with severity. Aim of our study to determine the correlation of CRP and HbA1c in patients with Type 2 Diabetes mellitus. Materials and Method: This study was conducted through clinical and laboratory assessments at the Department of Biochemistry. Total 300 subjects are studied, 150 Type 2 Diabetic patients and 150 Non-diabetic subjects are studied in this study. Results: In present study we found that patient having T2DM with high HbA1c and high levels of CRP when compared to the control group. CRP levels in our study were significantly higher in type 2 diabetes patients compared to the Non-diabetic group. Keywords Diabetes mellitus, CRP, Inflammation, Glycosylated haemoglobin.